Frequency of Diabetes Mellitus in Thalassemia Major Patients - Fawad Ahmad, Iram Shehzadi, Adeen Zahoor (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study is to examine patients of major thalassemia and determine prevalence of diabetes mellitus among these cases. Study Design: Cross-sectional Place and Duration: DHQ Teaching Hospital Sargodha.Dec 2020-May 2021 Methods: Total 200 hundred patients of major thalassemia with ages 15-45 years were included. After obtaining written consent from the patient, demographic information such as age, sex, and body mass index were gathered. Fasting blood samples were used to estimate the FBS. Medical records were used to collect clinical and laboratory data, such as counts of red blood cells, Hb levels before transfusion, and five-year ferritin levels. Chi-square, student t-tests, and logistic regressions were used for statistical analysis. The whole set of data was analysed with SPSS 24.0. Results: In major thalassemia patients majority of the cases were females 120 (60%) and 80 (40%) were total males. Mean age of the patients was 21.6±8.23 years and had mean BMI 20.5±9.19 kg/m2. Frequency of DM among major thalassemia cases were 18 (9%). Mean five year ferritin among cases was 5214.3±2531 ng/ml. Among 18 cases of DM most of the patients were males 12 (66.7%) and 6 (33.3%) were females. Patients with ages >25 years and ferritin value >6000 ng/ml had increased risk of DM. Mean blood transfusion in DM patients was 2.9±3.66 U/mo with mean duration 15.8±4.17 years. Conclusion: We found from this study that the prevalence of diabetes in major thalassemia patients was 9 percent, with the majority of cases being male. We believe this is attributable to older age, a higher mean five-year ferritin level, and a greater amount of blood transfused.